Epidemiology of sports injuries in Korean elite female fencing athletes: a prospective cohort study - Kim, H. C.; Park, K. J. (Revista Brasileira de Medicina do Esporte, 2023)
Objectives: We aimed to assess the risk of injury associated with training activities of Korean elite female fencing athletes by weapon category. Methods: We prospectively collected 2021 data on 80 elite female fencing athletes at the Korean Training Center. Injury incidence rates were expressed as Poisson rates with a 95% confidence interval. We used ?2 tests to compare injury locations and recovery times by weapon category. Results: A total of 233 injuries were recorded, averaging 3.27 (95% CI, 2.86-3.72) injuries per 1,000 training hours. The sabre had the highest injury incidence rate, followed by the epee and the foil. Injuries to fencing athletes were the most common in the lower extremities (46.35%), followed by the upper extremities (24.03%), trunk (20.17%), and head and neck area (9.44%). The weapon category did not affect the body regions (p=0.425). However, recovery time differed significantly by body region (p=0.021). Conclusions: The weapon category was found to affect the injury incidence rate. In addition, recovery time varied depending on body region. Further research is needed to clarify these results.